2020
DOI: 10.1177/1321103x19899171
|View full text |Cite
|
Sign up to set email alerts
|

‘Just notes’: Young musicians’ perspectives on learning expressive performance

Abstract: Expressiveness is an important aspect of an excellent music performance as it adds quality and interest to the playing and listening experience. Although several studies have investigated tertiary students’ learning of expressiveness, little is known about effective approaches for teaching children to perform expressively. In the present project, 16 young musicians (aged 9–16, with performance levels at Pre-Grade 1 – Grade 8) took part in a video-stimulated recall interview after an experimental investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The questions regarding musical character had facilitated their reflection on, and understanding of the interpretation, thus contributing to their learning of expressiveness. Findings from the experimental and the VSRI study demonstrate the usefulness of teachers’ enquiry and learners’ reflection for young musicians’ learning of EMP ( Meissner, 2018 , 2020 ; Meissner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…The questions regarding musical character had facilitated their reflection on, and understanding of the interpretation, thus contributing to their learning of expressiveness. Findings from the experimental and the VSRI study demonstrate the usefulness of teachers’ enquiry and learners’ reflection for young musicians’ learning of EMP ( Meissner, 2018 , 2020 ; Meissner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 83%
“…Recent studies have revealed that dialogic teaching consisting of enquiry and discussion is effective for enhancing children’s expressiveness as this can raise students’ awareness of and stimulate thinking about the musical character and how to convey this in performance. Young musicians reported that their teachers’ questions regarding the musical character were “eye-openers” as these served to shift their focus from the “technicality” to the “musicality” of pieces ( Meissner and Timmers, 2019 ; Meissner et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations